Mushaf Al-Qur'an Kuno di Museum Institut PTIQ Jakarta - Syatri, Jonni (Lajnah Pentashihan Mushaf Al-Qur'an, 2014)
This writing studies the uses of rasm, qiraat, the sign of reading and the sign of tajwid, as well as the sign of the division of the text in the four Quran manuscripts available at the Museum of the Institute of PTIQ Jakarta. In this writing, the writer tries to compare between one mushaf to another concerning the five problems mentioned above. Concerning the rasm, the writing will analyze if the mushafs being studied use rasm Usmaniy or imla'iy or the combination of both. As for the qiraat, the focus of the study is on the qiraat the copyist uses in the mushaf he has copied. The wiriting will also study the variety of the signs of writing, the sign of reading and the sign of tajwid (the science of reciting the Holy Quran) as well as the sign of the division of the text in those quran manuscripts. Keywords: Quran manuscript, rasm, qiraat, the sign of reading and the sign of tajwid, the sign of the division of the text.